Reptiles, amphibians and invertebrates : an identification and care guide - Bartlett, Patricia Pope, 1949-; Griswold, Billy; Bartlett, Richard D., 1938- (Hauppauge, N.Y. : Barron's, 2010)
From Back Cover Of Book: Reptiles, Amphibians, and Invertebrates an identification and card guide. Hundreds of color illustrations. Snake, lizards, insects, turtles and tortoises, frogs and toads, salamanders and newts, and arachnids are all featured in this book. It's a pictorial identification guide and husbandry manual covering more than 250 species, subspecies, and color morphs. The authors tell you what to look for when purchasing these animals and discuss caging and feeding. Each profile includes the animal's place of origin, its size from hatchling to adult, its lifespan, and its general behavior traits.
Introduction -- Part 1: Reptiles -- Snakes -- Boas and Pythons -- Colubrine Snakes -- Lizards -- Agamid Lizards -- Angiod Lizards: Alligator Lizards and Glass Lizards -- Chameleons -- Iguanian Lizards: Iguanas and relatives -- Armadillo Lizards and Plated Lizards -- Gekkonid Lizards -- Aeluroscalobotid Lizards -- Eublepharine Geckos: Eyelidded Geckos -- True Geckos -- Lacertid Lizards -- Skinks -- Teiid Lizards: Whiptails and Tegus -- Varanid Lizards: monitors -- Tortoises and Turtles -- Tortoises -- Mud Turtles and Musk Turtles -- Basking Turtles -- Side-necked Turtles -- Soft-shelled Turtles -- Crocodilians -- Caiman -- Part 2: Amphibians -- Frogs, Toads, and TreeFrogs -- Bombinatorids: Fire-bellied Toads -- Bufonids: True Toads -- Horned Frogs and relatives -- Dendrobatids: poison Frogs -- Hylid Frogs: Australian and American TreeFrogs -- Hyperoliid Frogs -- Leptopelid Frogs -- Mantellas -- Malayan Horned Frog -- Microhyulids: Narrow-mouthed Toads -- Pipid Frogs -- Ranids: True Frogs -- Rhacophorids: Gliding Frogs and relatives -- Newts, Salamanders, and Caecilians -- Ambystomatids: Mole Salamanders -- Salamandrids: Newts -- Caecilians -- Part 3: Invertebrates -- Arthropods -- Tarantulas -- Millipedes and Centipedes -- Scorpions -- Mantids and Stick Insects -- Cockroaches -- Bibliography -- Index.
Includes bibliographical references (p. 273-274) and index.
Keywords: Amphibians as pets; Reptiles as pets; Invertebrates as pets